2012
DOI: 10.1021/es204622m
|View full text |Cite
|
Sign up to set email alerts
|

Duty Cycling Influences Current Generation in Multi-Anode Environmental Microbial Fuel Cells

Abstract: Improving microbial fuel cell (MFC) performance continues to be the subject of research, yet the role of operating conditions, specifically duty cycling, on MFC performance has been modestly addressed. We present a series of studies in which we use a 15-anode environmental MFC to explore how duty cycling (variations in the time an anode is connected) influences cumulative charge, current, and microbial composition. The data reveal particular switching intervals that result in the greatest time-normalized curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 64 publications
2
25
0
Order By: Relevance
“…The capacitor was charged for hours but discharged for only less than a minute, which indicated that electroactive species around the electrode was replenished while the capacitor was being discharged. Gardel et al [9] obtained similar results with duty cycling based energy harvesting from a multianode MFC, which suggests that it was necessary to replenish depleted electron donors within the biofilm and surrounding diffusion layer to maximum charge transfer. Grondin et al [10] also investigated the power output as a function of duty cycle, but the effect of extraction frequency was not studied.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The capacitor was charged for hours but discharged for only less than a minute, which indicated that electroactive species around the electrode was replenished while the capacitor was being discharged. Gardel et al [9] obtained similar results with duty cycling based energy harvesting from a multianode MFC, which suggests that it was necessary to replenish depleted electron donors within the biofilm and surrounding diffusion layer to maximum charge transfer. Grondin et al [10] also investigated the power output as a function of duty cycle, but the effect of extraction frequency was not studied.…”
Section: Introductionmentioning
confidence: 75%
“…In this study, we investigated the energy extraction with different inductances, duty ratios, and switching frequencies to characterize how these parameters affect MFC energy output performance. The energy harvesting frequency or switching frequency of the power converter ranges from 100 to 5000 Hz, which means that our switching periods (10 msece200 msec) were orders of magnitude shorter than previous studies, which were in the range of hours [8], minutes [12] and seconds [9,10].…”
Section: Introductionmentioning
confidence: 79%
“…Recently, some strategies based on intermittent connection/disconnection operation were used to modulate the anode potential duration [24], external resistance loading [25,26] and MFC voltage [27]. However the current was still a dependent parameter in those reported strategies.…”
Section: Current Adaptation For Robust Electro-active Biofilmsmentioning
confidence: 99%
“…However, when bio-anodes were subjected to a continuous limiting current, the anode potential would be rapidly polarized to more positive potentials beyond that suitable for microbial growth, enabling the current-adaptive growth failure. Some strategies based on intermittent connection/disconnection operation were recently developed to modulate the anode potential duration [24], external resistance loading [25,26] and MFC voltage [27]. Inspired by these studies, intermittent limiting anodic currents (ILACs) application was designed to stimulate the current-adaptive growth of anodic biofilms for the first time in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Several energy harvesting strategies have emerged in literature. Two predominant strategies involve either a potentiostatic operation [12][13][14][15][16][17] or a capacitor charging operation. 5,7,[18][19][20][21] In SMFC applications, the cell potential -the difference between cathode and anode potentials-can be kept constant manually adjusting the external load or automatically by using electronic feedback control.…”
mentioning
confidence: 99%